INVESTIGASI PENERAPAN PEMBELAJARAN BERBASIS ICT - Hayati, Rita; Mulyaningsih, Endang (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to 1) find out the strategies used to implement ICT-based learning in the Rotan 1 National High School; 2) find out the challenges and obstacles in their application. This research was conducted using inductive qualitative methods. Data collection is done by interview, observation, documentation study, and study of research results. The results of the study indicate that the strategies used to implement ICT-based learning include 1) Multimedia-Based Presentation Learning; 2) Learning through video media; 3) Blended e-Learning. While the obstacles and challenges faced include 1). Lack of equipment availability and maintenance funds; 2). Poor infrastructure; 3) hidden curriculum is difficult to develop.